2018
DOI: 10.1186/s13195-018-0345-3
|View full text |Cite
|
Sign up to set email alerts
|

A language-based sum score for the course and therapeutic intervention in primary progressive aphasia

Abstract: BackgroundWith upcoming therapeutic interventions for patients with primary progressive aphasia (PPA), instruments for the follow-up of patients are needed to describe disease progression and to evaluate potential therapeutic effects. So far, volumetric brain changes have been proposed as clinical endpoints in the literature, but cognitive scores are still lacking. This study followed disease progression predominantly in language-based performance within 1 year and defined a PPA sum score which can be used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Thus, cortical ROI measures such as the PSTC R may be useful for future clinical trials and may allow for smaller sample sizes to detect a significant effect. Intriguing summary scores of language performance are emerging [10] and may be useful to detect change as they are optimized. Understanding consistency of these measures at the individual level over the disease course is important before they can be reliably introduced as clinical trial outcome metrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cortical ROI measures such as the PSTC R may be useful for future clinical trials and may allow for smaller sample sizes to detect a significant effect. Intriguing summary scores of language performance are emerging [10] and may be useful to detect change as they are optimized. Understanding consistency of these measures at the individual level over the disease course is important before they can be reliably introduced as clinical trial outcome metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Determinants of the pace of decline in PPA are incompletely understood, especially whether the presence of AD versus non-AD pathology influences the rate of deterioration. This is in part because of a dearth of prospective longitudinal investigations [8][9][10][11][12][13][14] relative to crosssectional investigations and the historic lack of in vivo neuropathologic biomarkers. Disease duration estimates for individuals with PPA range from 3 to 20 years, highlighting the individual variability in progression rates.…”
Section: Introductionmentioning
confidence: 99%
“…A total of n = 106 subjects and their volumetric data of up to three timepoints (V1 to V3) was finally included in this study. Data were collected between 2011 and 2018 from 10 German sites (Bonn, Erlangen, Göttingen, Hamburg, Homburg/Saar, Leipzig, Munich, Rostock, Ulm, Würzburg); data subsets have been used previously 29,30 …”
Section: Methodsmentioning
confidence: 99%
“…Each study visit included a neurological and an extensive neuropsychological protocol (for details see Semler et al 29 29 indicated each patient's language abilities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation